Development of Podcast Media in Learning Digestive System Material in Senior High School: Design and Implementation - Putri, Ardea Mesitha; Helmita, Roza; Fajar, Najmiatul; Haviz, M (Bioeducation Journal, 2024)
This research is motivated by the condition of differences in students' levels of understanding of biology learning material which causes the learning process in class to become passive, apart from that students also have low interest in reading and rarely repeat learning material at home. The solution that the author offers is to develop additional audio-based learning media to help students learn independently outside the classroom. This learning media can be listened to by students whenever and wherever they are. The objectives of this research include analyzing the needs of teachers and students for the media being developed and to determine the validity and practicality of developing biology podcast media on class XI digestive system material. MIPA. The method used in this research is research and development (R&D) with a 4D approach (define, design, develop, and disseminate), but this research did not reach the dessiminate. The instruments used in this research were student needs analysis sheets for learning media development, validity test sheets, and practicality test sheets for Podcast media. Based on this research, the percentage of validity of podcast media was 86% in the very valid category, practicality by teachers was 85% in the very practical category, and practicality by students was 74% in the practical category. It can be concluded that the podcast media is in accordance with the needs of teachers and students and is ready and practical to use.